Manufacturing Continuous Improvement of Busbar Product Using Six Sigma Approach At PT.XYZ - Fithri, Prima; Nabila, Jihan; Triawan, Fandy; Armijal, Armijal (LPPM Universitas Andalas, 2022)
PT. XYZ is a manufacturing company engaged in the production of cables and conductors such as busbars. Busbar is a copper bar used to distribute electric power. The problem that occurs at PT. X is that there are still reject products in the busbar production The reject criteria found are as follows: bent busbar, scratched visual, oxidized visual, cracked visual during bending test. This aims of this research are to reduce the total rejects in busbar products by proposing improvements to the busbar production process using the six-sigma method. The data used in this study consisted of primary data (results of discussions with production managers, quality control managers and engineering staff and research in field) and secondary data types and total rejects within 21 months. The results of this research found that at the define stage scratched busbar and bent busbar are the dominant type of busbar that will be improved in this research. At the measure stage, the company sigma value is 3.607. This result can be used to propose quality improvement for the busbar production process whisch is obtained so that the company can reduce the number of defective products and improve product quality.